Kesadaran Diri dan Kaitannya Dengan Implementasi Pembentukan Karakter Peduli Lingkungan - Harahap, Mely Novasari (DIKLINKO JOURNALS PUBLISHER, 2025)
This writing discusses the importance of self-awareness in applying the culture of smiling, greeting, saluting, being polite, and being courteous in various contexts, whether in the workplace, education, or everyday life. The method used in this article is a literature study with a qualitative approach. Self-awareness in individuals is the ability to recognize, understand, and control their own emotions and behaviors in social interactions. By enhancing self-awareness, individuals are able to apply the principles of the culture of smiling, greeting, saluting, being polite, and being courteous, which in turn improves communication, strengthens interpersonal relationships, and creates a more positive atmosphere. When almost all educational and learning implementation units carry out their vision and mission, several phenomena are found in the field indicating that the next generation or students lack character. The learning experiences in schools that are clearly designed to develop cognitive, affective, and psychomotor aspects are felt to be less 'touching' for the students. This is related to attitude learning and, more specifically, starts from something simple yet difficult to implement, which is having good awareness. The attitude learning referred to is a learning experience related to the field of attitudes, which includes self-awareness training, multicultural understanding, and mastery of life skills.